GameAlfa: guia didático instrucional - Santos, Austonio Queiroz dos (Brasil, 2019)
The GameAlfa is a digital game made to serve as a facilitator resource of alphabetization through the development of phonological awereness skills in children with ages between six and eight years old. It can be played in different operational sistems and equipments, online and offline. This guide presents the GameAlfa and teaches its use, since the getting process, the instalation and operational process, as well as suggesting a pedagogical activity. We hope that this material serves for the introduction of this digital resource in classes allowing a contextualized and significant learning for the children.